Numerical modeling of RC column reinforced by new strategy using fiberglass tape and cloth - Aissa Boumedjane; Saadi Mohamed; Yahiaoui Djarir; noureddine Lahbari (The Journal of Engineering and Exact Sciences)
This paper presents the results of finite element analysis (FE) to study the axial compression behavior of reinforced concrete columns wrapped with tapes and fiberglass cloths according to different techniques using ABAQUS software. In the beginning, columns are modeled as 3D solid elements with a concrete damage plasticity model (CDPM), as the columns in this study are considered to be low compressive strength reinforced concrete and the rebar as 3D mesh elements. And once assembled, the specimen is wrapped with tape and cloth in the form of three-dimensional shell elements. Then, in order to analyze the behavior of the ultimate loads, the deformation of the confinement material, and the distribution of deformations in the concrete, the controlled displacement method used to apply the uniaxial compression loads to the specimen. Finally, a new mixed confinement model between partial confinement and complete has been proposed using a database of the results of a numerical simulation for confined concrete by fiberglass tapes and cloths. And it was found that the confinement strategy proposed in this study is very effective for the behavior of the reinforced concrete column, as the stress decreases significantly with the expansion and widening of the confinement stiffness of concrete in the plastic phase which improves the axial stress resistance.